Avaliação da tecnologia social de captação de água da chuva numa perspectiva agroecológica - Machado, Rosali Bandeira Carvalho dos Santos (2016)
This work aims to evaluate the Social Technology of rainwater storage in demonstration units for multiple uses in agroecological perspective. In this regard, evaluation indicators were developed. The various moments of dialogue done with the social actors involved and the coordinators of the Project TSGA were needed to identify their needs and expectations regarding the use of rainwater storage system. Based on this, the main elements of evaluation of Social Technology were established: the social demands of the community mobilization and community participation, ownership and learning by the social actors, participatory planning, building knowledge from relationship theory / practice, economic and environmental sustainability and reapplicability, which were assessed through questionnaires and interviews, seeking a interdisciplinary and systemic vision. The research found that the quality of rainwater captured, does not comply with the criteria required by regulatory standards, relative to total coliforms, Escherichia coli, pH and turbidity. In analyzing the evaluation indicators of Social Technology rainwater storage was observed that the water quality, water availability, mobilization and community participation and participatory planning have note equal to 2, which means that the answers to these indicators were partially satisfactory. For the remaining indicators, all demonstration units the note was equal to 3, therefore classified as fully satisfying. The units were evaluated according to presupposeds of Social Technologies effectiveness, feasibility and simplicity recommended by TSGA Project. Regarding the effectiveness of the Social Technology rainwater captured, it was verified the efficiency and efficacy in all units on the system management and the empowerment of social actors involved; however, it was not observed efficacious according to water quality and full efficiency of the amount of colleted water. In relation to feasibility of TS CAC, it was found that the materials for the construction of the systems are easily found in their regions and social actors have ease in management system. Additionally, it was observed that the design of captation and distribution of rainwater is viable and attractive economically and a low risk, thus determining the viability of social technology. Regarding the simplicity of TS CAC, all social actors involved in the four units studied understood the functioning of the system, have the ability to build and are able to multiply the knowledge of this technology, so much in planning the same, as well as in assembly and use.